Compliance na administração pública federal: instrumento de governança, gestão de riscos e sustentabilidade - Gercwolf, Susana (2019)
This research investigates the use of compliance in the Brazilian Public Administration and its pillars of governance, risk management and sustainability. In order to do so, the research is supported by domestic and foreign bibliographical references, as well as the current legislation. The dissertation problematizes the challenges that the effective use of compliance faces in the public environment, considering the difficulties of multiinstitutional articulation involving control, given the existing asymmetric information. Ultimately, the research seeks to align the challenge of boosting public compliance with the potential use of blockchain in control and aims to contribute towards the reflection of the theme with the formulation of propositional suggestions aiming to improve the monitoring of public sector compliance.